PENGUATAN KEBIJAKAN PUBLIK USAHA PENGENTASAN KEMISKINAN MELALUI PENGEMBANGAN INDUSTRI MIKRO OLAHRAGA* - Kristiyanto, Agus (Universitas Muhammdaiyah Surakarta, 2011)
The research aims to describe a factual account of the various responses of actual perpetrators of the real sector micro-sports industry. Dimensions are expressed related to the growth of the business climate has been done by Government and Local Government, especially for poverty alleviation through the sports industry. Conclusions: Satisfaction micro business sports industry on the performance of Local Government on eight dimensions varied business climate, sports industry in fact just giving a side job for some people, but has not been a big impact for poverty reduction. Business expectations: to contribute to alleviating poverty, the sports industry business developed specifically for quality, Social protection and security should be given to the perpetrators of the sports industry business, clear policy regarding the development of micro industries important sport once to strengthen the real sector, technical assistance by the government is required by the real sector of the sports industry.